The Effect of Based E-learning Contextual Approach on Student Learning Motivation - Ilyas Ilyas; An Nisaa Al Mumin Liu (Postgraduate, University of Mataram, 2020)
One of the fundamental problems for students is the low motivation to learn. The reason is the learning approach used by lecturers in the classroom is less attractive. Therefore this study about the use of contextual approaches based on e-learning to help student motivation. This type of research is quantitative research, with descriptive statistical analysis and inferential statistics to describe motivation data for learning simple harmonic wave material Students of Physics Education Study Program at University of Flores use a contextual approach based on e-learning. Data collection techniques used in this study were non-test techniques. From the results of descriptive analysis shows that the average student learning motivation is 78.90 in the sufficient category. While the results of inferential statistics show the t value of 5.453, sig (2-tailed) 0.000. Because the sig (2-tailed) value of 0,000 is smaller than 0.05, this shows that the contextual approach based on e-learning (Zoom Cloud Meeting) influences student learning motivation